2019
DOI: 10.1016/j.diabres.2019.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Variation in process quality measures of diabetes care by region and institution in Japan during 2015–2016: An observational study of nationwide claims data

Abstract: A B S T R A C TAims: To calculate process quality measures of diabetes care in Japan using nationwide exclusive claims database.Methods: Using the National Database of health insurance claims during 2015-2016, the proportions of outpatients who received recommended examinations at least annually https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Insurance claims databases have been increasingly used for studies to identify risk factors for cardiovascular disease and to compare the effectiveness of drugs in treating cardiovascular disease 6‐8 . Recently, studies using claims data have increased in the field of diabetes in Japan 9‐17 . In Japan claims data are recorded electronically using unique master codes 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Insurance claims databases have been increasingly used for studies to identify risk factors for cardiovascular disease and to compare the effectiveness of drugs in treating cardiovascular disease 6‐8 . Recently, studies using claims data have increased in the field of diabetes in Japan 9‐17 . In Japan claims data are recorded electronically using unique master codes 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, regular visits to ophthalmologists are important. However, a recent survey found that fewer than half of Japanese patients with diabetes had had an ophthalmologic consultation within 1 year [10]. The reasons for inadequate visits to ophthalmologists included long waiting times on the day of the visit, high examination costs, and the inability to undergo an examination near home [11].…”
Section: Discussionmentioning
confidence: 99%
“…Sugiyama et al reported that 46.5% of 4,154,452 outpatients who were treated with regular antidiabetic medications, underwent a retinopathy examination at least annually, according to the National Database of Health Insurance Claims from 2015 to 2016 [10]. The ophthalmologic consultation rate within 1 year was 48% for patients with diabetes who were evaluated at an Internal Medicine Department, which was almost the same as the receipt-based result of Sugiyama et al [10]. The frequency of ophthalmologic visits was correlated negatively with age, HbA1c, duration of diabetes, and severity of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously used the National Database to create retrospective sample cohorts of > 100 million individuals with a very small selection bias, and thus, good generalizability 9 The National Database contains health data on an extremely large population, which enables epidemiological studies of relatively rare conditions to be conducted with good statistical power. The National Database has been used to obtain real-world health-related evidence of global relevance [10][11][12][13][14] Using a large national database, this population-based study aimed to determine whether there is an association between the onset of type 1 diabetes and a diagnosis of influenza. To this end, we used a self-controlled case series method that enabled us to evaluate the effects of specific environmental factors on the onset of type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%